Social and psychological aspects of the influence of stereotypes on the behaviour of consumers on the Russian market - Shumilova, Svetlana; Kašparová, Eva, 1958-; Surynek, Alois, 1954-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The goal of this work is to explore the sociological and psychological problems of having stereotypes of behaviour on the Russian market in the study group, its cultural aspects, and the model consumer decision at the time of acquaintance with the goods.The theoretical part of this work will be based on sociological and psychological theories, marketing studies and concepts, cultural specifics, and influence of them to people. The methodology part is dealing with the research of Russian consumers of the study group.
Vedoucí práce: Eva Kašparová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses